Phenomenology of Social Integration and Social Exclusion. An Essential Task of Political Collective Agency - Marco Di Feo (Rosenberg & Sellier, 2019)
In this paper the author is going to talk about an essential task of political agency: social integration. He analyzes it from a phenomenological perspective, identifying its essential elements in order to achieve an eidetic view of it. The author roots the analysis of social integration in a stratified view of the social world that appears essentially composed of four different forms of social interaction: community interaction, characterized by solidarity relationships; territorial interaction, characterized by “conflicting” relationships (polemos); social interaction, based on standard models of behavior; and institutional interaction, based on laws that govern the public life. Social integration is stratified into these four forms of intersubjective life and is fully achieved only if it allows a real state of belonging and an actual participation in each of them. The policy plays a crucial role because integration is often a critical process that can cause social conflicts and that can not simply be left to the sensibility and will of those who live in the various contexts. Political agency should coordinate normative and cultural actions, so that norms are not simply imposed, but are assimilated by a citizenship aware of the social, ethical and political value of integration.